STRATEGI PENANGANAN KEKERASAN SEKSUAL MELALUI UPAYA NON-PENAL - Eleanora, Fransiska Novita; Lestari, Melanie Pita; Ismail, Zulkifli (JURNAL HUKUM DAS SOLLEN, 2024)
The purpose of this writing is to find out and analyze strategies for dealing with sexual violence through non-penal efforts. Acts of sexual violence is a crime that violates human rights and the political direction of Indonesian law has given fresh air to efforts to overcome sexual violence, but of course the efforts made cannot only be carried out through penal efforts, but non-penal efforts also need to be taken as a strategy. handling sexual violence. Where non-penal efforts are also made so that a person is aware or growing awareness to avoid actions in the form of crimes of decency or sexual violence which consequently have an impact on violations of the rule of law and can be given criminal sanctions for those proven guilty. Therefore, the problem to be discussed in this paper is how to deal with sexual violence through non-penal efforts. Based on the research results, non-penal efforts that can be carried out include activities such as sponsorship and social education in the context of developing community social responsibility, cultivating community mental health through moral, religious education, and so on. This also includes activities in the framework of increasing child and youth welfare efforts, continuous monitoring activities by the police, security forces, and so on. Keywords: violence, sexual, non penal efforts